Parent-Child Assessment of Strengths and Difficulties of German Children and Adolescents Born With Esophageal Atresia - Witt, Stefanie; Dingemann, Jens; Dellenmark-Blom, Michaela; Quitmann, Julia (Frontiers in Pediatrics, 2021)
Introduction/aim: Children and adolescents with a chronic somatic disease have a higher risk of developing psychological disorders than healthy peers. Therefore, we aim to investigate internalizing and behavioral problems in pediatric patients with esophageal atresia (EA) and compare this sample with German reference values using both childrens' self-reports and parents' proxy reports. Methods: The present cross-sectional study is part of the German-Swedish EA-QOL study developing a condition-specific instrument to assess Health-related Quality of Life (HrQoL) in children and adolescents born with EA from both self and proxy perspectives. The current analyses use data from the German sample collected within the field test phase. Participants were enrolled from the Medical School Hannover (MHH) and "Auf der Bult" Children's Hospital, Hannover. The cooperating clinicians provided the medical records while socio-demographic information was collected through the parent-report within the questionnaires. We used the Strengths and Difficulties Questionnaire (SDQ) to measure internalizing and behavioral problems of children and adolescents born with EA ranging from 2 to 18 years. Results: A total of 51 families participated in the field test phase. Eighty-eight parent reports and 22 child reports were included in the analyses. While the parents' perspective from the SDQ leads to a higher percentage of abnormal or borderline behavior, there is no difference to the reference group from the children's perspective. Conclusion: Incorporating routine psychological assessment into pediatric health care can help improve understanding of the burden of illness, examine treatment outcomes, assess the quality of care, and tailor interventions to meet patient and parent needs. Involving the whole family can help develop appropriate and functional coping strategies. From our point of view, it is necessary to address parental needs and concerns as well in order to provide the best possible holistic development in the family system. The family is the basis for the children's successful development, especially for children with special health care needs.